Al-Asma’ al-Husna dalam Wacana Akidah - Hamat, Mohd Fauzi; Shuhari, Mohd Hasrul (Afkar: Jurnal Akidah dan Pemikiran Islam, 2010)
Allah has beautiful names, known as al-Asma’ al-Husna. Understanding God’s names is a basic requirement for achieving the ma‘rifatullah. The topic of al-Asma’ al-Husna, which is one of the topics being discussed in al-ilahiyyat, has often been dealt with by Muslim theologians. This article describes the views of Muslim theologians from the Ash’arite school of thought. It first explains how the understanding of al-Asma’ al-Husna can help people to achieve ma‘rifatullah based on the Qur‘an and the Sunnah. This paper concludes that the discourse of al-Asma’ al-Husna has a major position in the works of Muslim theologians such as al-Juwayni (d. 478H), al-Ghazali (d. 505H) and Fakhr al-Din al-Razi (d. 606H). In their work, they focused on the concept of al-Asma’ al-Husna, the classification of the names of God and the importance of al-Asma’ al-Husna for developing human character.